Shocking the conscience of humanity : gravity and the legitimacy of international criminal law - DeGuzman, Margaret M. (Oxford University Press, 2020)
The literature and jurisprudence of international criminal law relies on the claim that international crimes are exceptionally grave. DeGuzman looks to build the legitimacy of international law by exposing the value choices that the rhetoric of 'gravity' entails, and poses a new framework for assessing the legitimacy of international criminal law.